Song Copyright Law Reform in Indonesia - Westiartika, Dhira Taramadia; Abdulhamid, Muhammad; Nobel, Raden Muhammad; Fikri, Ahmad Ma’mun (LEGAL BRIEF, 2025)
Copyright on songs is one component of intellectual property rights that is philosophically based on the theory of naturalism and the theory of interests. However, in the Indonesian context, it also needs to be understood through the Marhaenism approach which emphasizes social justice. The National Collective Management Institution which was established based on Government Regulation Number 56 of 2021 and Law Number 28 of 2014 is tasked with managing copyright licenses. However, its existence raises various problems, including the potential for monopoly, lack of transparency, and limited access for independent music creators. The purpose of this study is to determine how copyright regulations are implemented in Indonesia. Using normative legal methods and secondary data, this study proposes a hybrid licensing model that will reform the copyright licensing system in Indonesia by implementing a progressive and responsive legal approach. This model will allow creators to choose between collective licenses and individual licenses based on digital technology. This reform is expected to realize distributive justice, more adaptive legal protection, and respect for the moral and economic rights of creators in a balanced manner